2021
DOI: 10.3390/biom12010009
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of BHB Testing on the Post-Mortem Diagnosis of Ketoacidosis

Abstract: Although beta-hydroxybutyrate (BHB) analysis has proved its importance in forensic pathology, its effects on cause-of-death diagnostics are unaddressed. Therefore, this study aims at evaluating the effects of BHB analysis on the number of deaths by DKA (diabetes ketoacidosis), AKA (alcoholic ketoacidosis), HHS (hyperosmolar hyperglycaemic state), hypothermia, diabetes, alcoholism, and acidosis NOS (not otherwise specified). All 2900 deaths from 2013 through 2019 in which BHB was analysed at the National Board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Of the three short-chain acylcarnitines identified in the present study, C4-OH has been previously reported to be associated with insulin resistance and type 2 diabetes mellitus [39]. Moreover, C4-OH is primarily generated from the corresponding ketone body-beta-hydroxybutyrate [40], which has been evaluated for its potential in identifying ketoacidosis in postmortem cases [41]. The study by Ahlström et al [41] and the current study have an overlap in cohorts; however, too few test cases classified as potentially hypo or hyper had beta-hydroxybutyrate analyses performed, presumably due to the lack of acidosis suspicion regarding the various causes of death.…”
Section: Acylcarnitine Profile As a Potential Marker For The Glycemic...mentioning
confidence: 78%
“…Of the three short-chain acylcarnitines identified in the present study, C4-OH has been previously reported to be associated with insulin resistance and type 2 diabetes mellitus [39]. Moreover, C4-OH is primarily generated from the corresponding ketone body-beta-hydroxybutyrate [40], which has been evaluated for its potential in identifying ketoacidosis in postmortem cases [41]. The study by Ahlström et al [41] and the current study have an overlap in cohorts; however, too few test cases classified as potentially hypo or hyper had beta-hydroxybutyrate analyses performed, presumably due to the lack of acidosis suspicion regarding the various causes of death.…”
Section: Acylcarnitine Profile As a Potential Marker For The Glycemic...mentioning
confidence: 78%
“…Moreover, BHB is used as marker for acidosis in forensic investigations with testing, at our institution in Sweden, increasing substantially in recent years. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Samples other than blood could also be alternative tools for diagnosing ketoacidosis. BHB measurement is the most important test to establish the diagnosis of postmortem ketoacidosis [22,23]. This is because that BHB should be stable even after death for a period of 24-72 h [24].…”
Section: Introductionmentioning
confidence: 99%